Protective Immune Responses Elicited by Fusion Protein Containing PsaA and PspA Fragments. (July 2015) - Lu, Jingcai; Sun, Tianxu; Wang, Dandan; Dong, Yunliang; Xu, Man; Hou, Hongjia; Kong, Franklin T.; Liang, Chunsu; Gu, Tiejun; Chen, Pinxu; Sun, Shiyang; Lv, Xiuping; et al.
<x xml:space="preserve">Abstract</x> Streptococcus pneumoniae is an important pathogen accounting for a large number of deaths worldwide. Due to drawbacks of the current polysaccharide-based vaccine, the most promising way to generate an improved vaccine may be to utilize protection-eliciting pneumococcal proteins. Pneumococcal surface adhesin A (PsaA) and pneumococcal surface protein A (PspA) are two vaccine candidates which have been evaluated against S. pneumoniae infection in animal models or human clinical trials with encouraging results. In this study, the efficacy of the fusion protein PsaA–PspA, which includes PsaA part and PspA part, in inducing immunoprotective effects against fatal pneumococcal challenge was evaluated in an animal model. PspA part of PsaA–PspA fusion protein contains both family1 N-terminal region and family 2 N-terminal clade-defining region of PspA. Immunization with the PsaA–PspA fusion protein induced high levels of antibodies against both PsaA and PspA, which could bind to intact S. pneumoniae strains bearing different PspAs. Ex vivo stimulation of splenocytes from mice immunized with PsaA–PspA induced IL-17A secretion. Mice immunized with PsaA–PspA showed reduced S. pneumoniae levels in the blood and lungs compared with the PBS group after intranasal infection. Finally, mice immunized with PsaA–PspA fusion proteins were protected against fatal challenge with pneumococcal strains expressing different PspAs regardless of the challenge route. These results support the PsaA–PspA fusion protein as a promising vaccine strategy, as demonstrated by its ability to enhance the immune response and stimulate production of high titer antibodies against S. pneumoniae strains bearing heterologous PspAs, as well as confer protection against fatal challenge with PspA family 1 and family 2 strains.